Self-repairing thermal barrier coating for gas turbine working blade and preparation method of self-repairing thermal barrier coating
By using the self-repair thermal barrier coating structure of the MCrAlY metal bonding layer, TiC-Al2O3-YSZ self-repair transition layer and YSZ ceramic layer on the gas turbine turbine working blades, the problems of excessive roughness of the coating surface and cumbersome process are solved, and the coating is self-repair and efficient heat insulation is achieved, which extends the service life and reduces production costs.
Patent Information
- Application Number
- CN202411596661.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing gas turbine turbine working blade thermal barrier coating is prone to problems such as excessive surface roughness, increased wind resistance coefficient, reduced output efficiency and carbon deposit after long operation. The process is cumbersome and the processing cycle is long, making it difficult to ensure quality stability.
The self-healing thermal barrier coating structure is adopted, including MCrAlY metal bonding layer, TiC-Al2O3-YSZ self-healing transition layer and YSZ ceramic layer, and is formed by supersonic flame spraying and plasma spraying. Combined with diffusion heat treatment, the process flow is simplified and the service life and reliability of the coating are improved.
It realizes the self-healing function of the coating, extends the service life of the coating, improves the thermal insulation performance and stress tolerance of the coating, reduces production costs, simplifies the process flow, and ensures the quality stability of the coating.
Smart Images

Figure CN119710523A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas turbine blade surface protection, and in particular relates to a self-repairing thermal barrier coating for a gas turbine turbine working blade and a preparation method thereof. Background Art
[0002] Thermal barrier coatings are usually double-layer or multi-layer structures consisting of a metal bonding layer with good oxidation resistance and corrosion resistance and a ceramic layer with low thermal conductivity. By coating the surface of parts with high-temperature resistant and high-insulation ceramic materials, the surface temperature of parts can be reduced and the service life of parts can be extended. Thermal barrier coatings have been widely used in aircraft engines and gas turbines. However, unlike aircraft engines, the operating cycle of gas turbines can reach 25,000 hours or even longer, which makes the reliability of thermal barrier coatings used on gas turbine blades particularly important. How to extend the service life of thermal barrier coatings and delay the failure of coatings is the key to designing and developing thermal barrier coating structures for gas turbines.
[0003] At present, the commonly used thermal barrier coating processing methods on the surface of gas turbine blades in China are: thermal spraying, vacuum arc plating, electron beam physical vapor deposition, etc. The thermal barrier coating of marine gas turbine blades usually uses electron beam physical vapor deposition to process the ceramic layer. The high strain tolerance of the feather columnar crystal structure ensures that the thermal barrier coating has a higher deformation in the hot and cold cycles, but the processing cycle is long and the blades undergo several high-temperature diffusion treatments. The thermal spraying method is usually used to process the ceramic layer of industrial ground gas turbine blades. The layered structure ensures that the thermal barrier coating has higher thermal insulation performance, but the ceramic coating is prone to cracks and fails quickly when facing hot and cold cycles.
[0004] Common coating materials on the surface of gas turbine blades are MCrAlY (M = Co, Ni or CoNi), PtAl and Y2O3 partially stabilized ZrO2 (abbreviated as YSZ), etc. The patent with publication number CN 109440046B proposes a method for preparing a thermal barrier coating on gas turbine blades, which uses supersonic spraying of MCrAlY bottom layer, plasma spraying of MCrAlY transition layer, vacuum diffusion, and finally plasma spraying of YSZ surface layer. It can be applied to the surface of turbine working blades to improve the service life of the coating. However, for gas turbine blades that need to run for a long time, the surface roughness of the coating exceeds 10μm, which will significantly increase the wind resistance coefficient of the turbine working blades, reduce the output efficiency, and carbon deposits are easily formed on the blade surface after long-term operation. The patent with publication number CN 107345229B proposes a coating processing method for sequentially using an MCrAlY bonding layer, an aluminide coating, an alumina coating and a ceramic layer on a gas turbine blade. The coating improves the high-temperature oxidation resistance and thermal corrosion resistance of the coating while ensuring the thermal insulation effect of the thermal barrier coating. However, the entire process involves multiple processes such as thermal spraying MCrAlY, electroplating platinum, chemical vapor deposition aluminizing, vacuum heat treatment and electron beam physical vapor deposition. The entire process is cumbersome and the processing cycle is long, making it difficult to ensure the quality stability of the coating in mass production. Summary of the invention
[0005] The object of the present invention is to provide a self-repairing thermal barrier coating for gas turbine turbine working blades and a preparation method thereof.
[0006] A self-repairing thermal barrier coating for a gas turbine turbine blade, comprising an MCrAlY metal bonding layer, a TiC-Al2O3-YSZ self-repairing transition layer and a YSZ ceramic layer sequentially on a high-temperature alloy substrate;
[0007] The TiC-Al2O3-YSZ self-repairing transition layer is a plasma sprayed layer of 20wt% TiC+xAl2O3+(80wt.%-x)YSZ;
[0008] The YSZ ceramic layer is a layered structure ceramic coating using pure tetragonal nano YSZ powder sprayed by plasma, or a feather columnar structure YSZ ceramic coating using electron beam physical vapor deposition.
[0009] Furthermore, the roughness of the MCrAlY metal bonding layer does not exceed 3 μm, and the porosity of the MCrAlY metal bonding layer is less than 2%.
[0010] Furthermore, the thickness of the TiC-Al2O3-YSZ self-repairing transition layer is 0.03-0.06 mm, and the porosity of the TiC-Al2O3-YSZ self-repairing transition layer is 5-15%.
[0011] Furthermore, the thickness of the pure tetragonal nano YSZ ceramic layer is 0.20-0.30 μm, and the thickness of the feather columnar YSZ ceramic layer is 0.20-0.250 mm.
[0012] A method for preparing a self-repairing thermal barrier coating for a gas turbine turbine blade comprises the following steps:
[0013] S1, degrease the surface of the parts using anhydrous ethanol or acetone;
[0014] S2, using sandblasting protective tape to protect the non-sprayed area of the blade;
[0015] S3, take the parts to be sprayed, use white corundum sand for dry sandblasting to complete surface roughening and activation;
[0016] S4, using supersonic flame spraying MCrAlY powder to form an MCrAlY metal bonding layer with a thickness of 0.08 to 0.12 mm;
[0017] S5, on the surface of the MCrAlY metal bonding layer, 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder is sprayed by atmospheric plasma to form a TiC-Al2O3-YSZ self-healing transition layer with a thickness of 0.03-0.06mm;
[0018] S6, preparing a YSZ ceramic layer with a thickness of 0.20-0.30 mm on the surface of the TiC-Al2O3-YSZ self-repairing transition layer to obtain a thermal barrier coating for gas turbine turbine blades. According to the working conditions of the gas turbine, it can be a pure tetragonal nano YSZ ceramic layer sprayed by plasma or a feather columnar YSZ ceramic layer deposited by electron beam physical vapor deposition;
[0019] S7, the coating is subjected to diffusion heat treatment in combination with the aging heat treatment system of the blade substrate, the heat treatment system is 1000-1060°C, and the insulation time is 2-5h.
[0020] Furthermore, in the S4, the particle size range of the MCrAlY powder is 5 to 38 μm, the components and mass percentages in the MCrAlY powder are Co: 20 to 26%, Cr: 18 to 23%, Al: 6.0 to 11.0%, Ta: 2.0 to 6.0%, Y: 0.3 to 0.6%, and the remainder is Ni and impurities. The spraying parameters of the MCrAlY metal bonding layer are: natural gas is used as the fuel gas, the natural gas flow rate is 155 to 200 NLPM, the oxygen flow rate is 210 to 270 NLPM, the shielding gas flow rate is 300 to 370 NLPM, the spraying distance is 200 to 300 mm, and the powder feeding rate is 35 to 60 g / min.
[0021] Furthermore, in the S5, the particle size range of the 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder is 30-60μm, and the components and mass percentages in the 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder are TiC: 20%, Al2O3 and YSZ powder totaling 80%, wherein 0.05≤x≤0.15, and the plasma spraying parameters of the TiC-Al2O3-YSZ self-repairing transition layer are: argon flow rate is 36-39NLPM, hydrogen flow rate is 8-11NLPM, current is 580-600A, voltage is 57-65V, spraying distance is 120-130mm, spraying power is 38-43kW, and powder feeding rate is 23-29g / min.
[0022] Furthermore, in S6, the plasma spraying parameters of the pure tetragonal nano YSZ ceramic layer are: argon flow rate is 39-45NLPM, hydrogen flow rate is 9-13NLPM, current is 600-630A, voltage is 65-75V, spraying distance is 90-120mm, spraying power is 39-47kW, and powder feeding rate is 23-29g / min.
[0023] Furthermore, in S6, the deposition parameters of the feather columnar YSZ ceramic layer by electron beam physical vapor deposition are: the deposition chamber pressure is lower than 0.5Pa, the oxygen flow rate is 90-180ccm, the voltage is 19-21kV, the heating current is 0.9-1.6A, the target feed rate is 0.56-0.82mm / min, the part rotation rate is 8-16rpm, and the part preheating temperature is 850-950℃.
[0024] Furthermore, in S7, after the thermal barrier coating is prepared, the coating is subjected to diffusion heat treatment, the heat treatment temperature is 1000-1060°C, the heating rate is 5-8°C / min, and the insulation time is 2-5h; then, the coating is cooled to 70°C by filling with argon gas and then taken out of the furnace.
[0025] The beneficial effects of the present invention are:
[0026] (1) The present invention adds a TiC-Al2O3-YSZ self-healing transition layer to a widely used double-layer thermal barrier coating structure to achieve a self-healing function. Many core-shell structures similar to capsule structures are evenly distributed in the coating. During high-temperature service, cracks in the coating expand and destroy the core-shell structure, inducing the TiC therein to react with O2, oxidizing to generate TiO2, which consumes crack propagation energy and squeezes the crack surface, passivates the crack tip, delays the crack propagation rate, and extends the service life of the coating.
[0027] (2) The thermal barrier coating preparation method formed by supersonic flame spraying MCrAlY metal bonding layer + plasma spraying TiC-Al2O3-YSZ self-healing transition layer + YSZ ceramic layer + diffusion heat treatment has a simpler and more efficient process, fewer thermal processes, and low production costs, while significantly improving the service life and reliability of the coating.
[0028] (3) The thermal barrier coating of the present invention not only has high thermal insulation and high stress tolerance, but also has crack self-repairing function, which can better resist short-term failure of the coating caused by rapid crack expansion in the coating.
[0029] (4) The preparation method of the present invention is simple and can be used to achieve stable mass production of self-repairing thermal barrier coatings for gas turbine turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a cross-sectional morphology diagram of the self-repairing thermal barrier coating prepared in Example 1 of the present invention;
[0031] Figure 2 This is a schematic diagram of the self-repairing thermal barrier coating prepared in Example 1 of the present invention undergoing a 1100°C thermal cycle resistance (water cooling test).
[0032] in Figure 2 a) is to test the initial coating morphology, Figure 2 b) is the coating morphology after 100 tests;
[0033] Figure 3 Schematic diagram of the self-repairing thermal barrier coating's resistance to thermal and cold cycles (air cooling) test 3000 times; DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the accompanying drawings.
[0035] In the following embodiments:
[0036] The components and mass percentages in MCrAlY powder are:
[0037] Co: 20-26%, Cr: 18-23%, Al: 6.0-11.0%, Ta: 2.0-6.0%, Y: 0.3-0.6%, the balance is Ni and unavoidable impurities;
[0038] The particle size range of NiCoCrAlY powder sprayed by HVOF is 5-38μm.
[0039] The components and mass percentages in 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder are TiC: 20%, Al2O3 and YSZ powder totaling 80%, where x=0.10.
[0040] 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder is obtained by mixing TiC nanoparticles, Al2O3 nanoparticles, and YSZ nanoparticles with a solvent and a binder according to weight percentage, grinding once, and then spray drying once to obtain a mixed powder, which is then sintered to obtain a mixture B, and then spray granulated after a second grinding. The spray powder is dried, sieved, etc.
[0041] 20wt%TiC+xAl2O3+(80wt.%-x)YSZ powder particle size range: D50=45μm;
[0042] The tensile bonding strength of the self-repairing thermal barrier coating for gas turbine blades is 31.1 to 43.9 MPa.
[0043] Embodiment 1:
[0044] The method for manufacturing the self-repairing thermal barrier coating for the turbine blades of a gas turbine described in this embodiment comprises the following steps:
[0045] S1, MCrAlY metal bonding layer spraying:
[0046] (1) Degreasing the surface of the directionally solidified alloy DZ411 used in the gas turbine using anhydrous ethanol or acetone to clean the dirt and grease on the surface of the substrate;
[0047] (2) Use sandblasting tape to shield and protect the non-spraying area, and use 60-80 mesh white corundum sand to dry sandblast the substrate surface at a sandblasting angle of 45-90° and a sandblasting pressure of 0.35-0.45 MPa to achieve the purpose of roughening and activating the substrate surface;
[0048] (3) The NiCoCrAlY coating was sprayed by supersonic flame spraying using Mecto DJ2700 equipment and natural gas as the fuel gas. The specific spraying parameters were set as follows: natural gas flow rate was 175 NLPM, oxygen flow rate was 245 NLPM, shielding gas flow rate was 350 NLPM, spraying distance was 240-260 mm, powder feeding rate was 48-52 g / min, and spraying thickness was about 0.120 mm;
[0049] S2, TiC-Al2O3-YSZ self-repairing transition layer spraying:
[0050] 20wt% TiC+10wt% Al2O3+70wt% YSZ powder was plasma sprayed on the surface of NiCoCrAlY coating to form a TiC-Al2O3-YSZ self-repairing transition layer. Metco F4 equipment was used, and the specific spraying parameters were set as follows: argon flow rate was 38NLPM, hydrogen flow rate was 10.5NLPM, current was 600A, voltage was 57-65V, spraying distance was 120-130mm, spraying power was 38-43kW, powder feeding rate was 23-29g / min, and spraying thickness was about 0.06mm;
[0051] S3, pure tetragonal nano YSZ ceramic layer spraying:
[0052] On the surface of the TiC-Al2O3-YSZ self-repairing transition layer, a pure tetragonal nano YSZ ceramic layer was plasma sprayed using Metco F4 equipment. The specific spraying parameters were as follows: argon flow rate was 42NLPM, hydrogen flow rate was 12.5NLPM, current was 620A, voltage was 70-75V, spraying distance was 100-120mm, spraying power was 44-47kW, and powder feeding rate was 23-25g / min;
[0053] S4, diffusion heat treatment:
[0054] After preparing the thermal barrier coating, the coating was subjected to diffusion heat treatment at a temperature of 1020°C. Before heating to 600°C, the heating rate was 8°C / min and the holding time was 30min. Before heating to 1020°C, the heating rate was 5°C / min and the holding time was 2h. Then, it was cooled with argon gas and taken out of the furnace after the temperature dropped to 70°C.
[0055] The cross-sectional morphology of thermal barrier coating is as follows: Figure 1 As shown, from Figure 1 It can be seen that the prepared self-healing thermal barrier coating has a three-layer coating structure, namely NiCoCrAlY metal bonding layer, TiC-Al2O3-YSZ self-healing transition layer and YSZ ceramic layer. The coating has a dense structure, the metal bonding layer has no obvious pores, the transition layer is tightly bonded to the metal bonding layer and the ceramic layer, and the pores between the YSZ ceramic layers are evenly distributed. Schematic diagram of the self-healing thermal barrier coating before and after the hot and cold cycle (water cooling) test is shown in Figure 2. Figure 2 As shown, from Figure 2 It can be seen that after the self-healing thermal barrier coating has been tested for 100 times in a hot and cold cycle (water cooling) at a heating temperature of 1100°C, the coating has a complete appearance and there is no warping or falling off at the edges.
[0056] Embodiment 2:
[0057] The method for manufacturing the self-repairing thermal barrier coating for the turbine blades of a gas turbine described in this embodiment comprises the following steps:
[0058] S1, MCrAlY metal bonding layer spraying:
[0059] (1) Degreasing the surface of the directionally solidified alloy DZ411 used in the gas turbine using anhydrous ethanol or acetone to clean the dirt and grease on the surface of the substrate;
[0060] (2) Use sandblasting tape to shield and protect the non-spraying area, and use 60-80 mesh white corundum sand to dry sandblast the substrate surface at a sandblasting angle of 45-90° and a sandblasting pressure of 0.35-0.45 MPa to achieve the purpose of roughening and activating the substrate surface;
[0061] (3) Supersonic flame spraying of NiCoCrAlY coating was performed using Mecto DJ2700 equipment, using natural gas as the fuel gas, and the specific spraying parameters were set as follows: natural gas flow rate was 175 NLPM, oxygen flow rate was 245 NLPM, shielding gas flow rate was 350 NLPM, spraying distance was 240-260 mm, powder feeding rate was 48-52 g / min, and spraying thickness was 0.120 mm;
[0062] S2, TiC-Al2O3-YSZ self-repairing transition layer spraying:
[0063] 20wt% TiC+10wt% Al2O3+70wt% YSZ powder was plasma sprayed on the surface of NiCoCrAlY coating to form a TiC-Al2O3-YSZ self-repairing transition layer. Metco F4 equipment was used, and the specific spraying parameters were set as follows: argon flow rate was 38NLPM, hydrogen flow rate was 10.5NLPM, current was 600A, voltage was 57-65V, spraying distance was 120-130mm, spraying power was 38-43kW, powder feeding rate was 23-29g / min, and spraying thickness was 0.06mm;
[0064] S3, electron beam physical vapor deposition feather columnar YSZ ceramic layer:
[0065] (1) On the surface of the TiC-Al2O3-YSZ self-repairing transition layer, the coating surface roughness is reduced to Ra < 1.0 μm by mechanical polishing or vibration polishing, the parts are cleaned by ultrasonic wave, and then blown clean and dried with compressed air;
[0066] (2) On the surface of the TiC-Al2O3-YSZ self-repairing transition layer, a feather columnar YSZ ceramic layer was deposited using electron beam physical vapor deposition. The UE207X electron beam physical vapor deposition equipment was used. The specific deposition parameters were set as follows: the vacuum chamber was pumped to 1×10 -2Pa, open the gate valve, introduce high-purity oxygen, the oxygen flow rate is 150ccm, keep the deposition chamber pressure below 0.5Pa, preheat the parts, the part preheating temperature is 900℃, the preheating time is 30-35min, the voltage is 19-21kV, the heating current is 0.9-1.6A, the target feed rate is 0.56-0.82mm / min, the part rotation rate is 16rpm, the target consumption is 35mm-40mm, turn off the heating current, and the parts are cooled to below 200℃ and taken out of the furnace.
[0067] S4, diffusion heat treatment:
[0068] After preparing the thermal barrier coating, the coating was subjected to diffusion heat treatment at a temperature of 1020°C. Before heating to 600°C, the heating rate was 8°C / min and the holding time was 30min. Before heating to 1020°C, the heating rate was 5°C / min and the holding time was 2h. Then, it was cooled with argon gas and taken out of the furnace after the temperature dropped to 70°C.
[0069] Schematic diagram of the self-repairing thermal barrier coating before and after the hot and cold cycle (air cooling) test Figure 3 As shown, from Figure 3 It can be seen that after the self-healing thermal barrier coating has been tested for 3000 times in the hot and cold cycle (air cooling) at a heating temperature of 1100°C, the coating has a complete appearance and there is no warping or falling off at the edges.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A self-repairing thermal barrier coating for a gas turbine blade, characterized in that: It includes an MCrAlY metal bonding layer, a TiC-Al2O3-YSZ self-repairing transition layer and a YSZ ceramic layer on a high-temperature alloy substrate in sequence; The TiC-Al2O3-YSZ self-repairing transition layer is a plasma sprayed layer of 20wt% TiC+xAl2O3+(80wt.%-x)YSZ; The YSZ ceramic layer is a layered structure ceramic coating using plasma spraying of pure tetragonal nano YSZ powder, or a feather columnar structure YSZ ceramic coating using electron beam physical vapor deposition.
2. The self-repairing thermal barrier coating for a gas turbine blade according to claim 1, characterized in that: The roughness of the MCrAlY metal bonding layer does not exceed 3 μm, and the porosity of the MCrAlY metal bonding layer is less than 2%.
3. The self-repairing thermal barrier coating for a gas turbine blade according to claim 1, characterized in that: The thickness of the TiC-Al2O3-YSZ self-repairing transition layer is 0.03-0.06 mm, and the porosity of the TiC-Al2O3-YSZ self-repairing transition layer is 5-15%.
4. The self-repairing thermal barrier coating for a gas turbine blade according to claim 1, characterized in that: The thickness of the pure tetragonal nano YSZ ceramic layer is 0.20-0.30 μm, and the thickness of the feather columnar YSZ ceramic layer is 0.20-0.250 mm.
5. A method for preparing a self-repairing thermal barrier coating for a gas turbine turbine blade according to claim 1, comprising the following steps: S1, degrease the surface of the parts using anhydrous ethanol or acetone; S2, use sandblasting protective tape to protect the non-sprayed area of the blade; S3, take the parts to be sprayed, use white corundum sand for dry sandblasting to complete surface roughening and activation; S4, using supersonic flame spraying MCrAlY powder to form an MCrAlY metal bonding layer with a thickness of 0.08 to 0.12 mm; S5, on the surface of the MCrAlY metal bonding layer, 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder is sprayed by atmospheric plasma to form a TiC-Al2O3-YSZ self-healing transition layer with a thickness of 0.03-0.06mm; S6, preparing a YSZ ceramic layer with a thickness of 0.20 to 0.30 mm on the surface of the TiC-Al2O3-YSZ self-repairing transition layer to obtain a thermal barrier coating for gas turbine working blades. According to the gas turbine operating conditions, it can be a pure tetragonal nano YSZ ceramic layer sprayed by plasma or a feather columnar YSZ ceramic layer deposited by electron beam physical vapor deposition; S7, the coating is subjected to diffusion heat treatment in combination with the aging heat treatment system of the blade substrate, the heat treatment system is 1000-1060°C, and the insulation time is 2-5h.
6. The method for preparing a self-repairing thermal barrier coating for a gas turbine blade according to claim 5, characterized in that: In the S4, the particle size range of MCrAlY powder is 5-38μm, the components and mass percentages in the MCrAlY powder are Co: 20-26%, Cr: 18-23%, Al: 6.0-11.0%, Ta: 2.0-6.0%, Y: 0.3-0.6%, and the remainder is Ni and impurities. The spraying parameters of the MCrAlY metal bonding layer are: natural gas is used as the fuel gas, the natural gas flow rate is 155-200NLPM, the oxygen flow rate is 210-270NLPM, the shielding gas flow rate is 300-370NLPM, the spraying distance is 200-300mm, and the powder feeding rate is 35-60g / min.
7. The method for preparing a self-repairing thermal barrier coating for a gas turbine blade according to claim 5, characterized in that: In the S5, the particle size range of 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder is 30-60μm, and the components and mass percentages in the 20wt% TiC+xAl2O3+(80wt.%-x)YSZ powder are TiC: 20%, Al2O3 and YSZ powder total 80%, wherein 0.05≤x≤0.15, and the plasma spraying parameters of the TiC-Al2O3-YSZ self-repairing transition layer are: argon flow rate is 36-39NLPM, hydrogen flow rate is 8-11NLPM, current is 580-600A, voltage is 57-65V, spraying distance is 120-130mm, spraying power is 38-43kW, and powder feeding rate is 23-29g / min.
8. The method for preparing a self-repairing thermal barrier coating for a gas turbine blade according to claim 5, characterized in that: In S6, the plasma spraying parameters of the pure tetragonal nano YSZ ceramic layer are: argon flow rate is 39-45NLPM, hydrogen flow rate is 9-13NLPM, current is 600-630A, voltage is 65-75V, spraying distance is 90-120mm, spraying power is 39-47kW, and powder feeding rate is 23-29g / min.
9. The method for preparing a self-repairing thermal barrier coating for a gas turbine blade according to claim 5, characterized in that: In S6, the deposition parameters of the feather columnar YSZ ceramic layer by electron beam physical vapor deposition are: the deposition chamber pressure is lower than 0.5Pa, the oxygen flow rate is 90-180ccm, the voltage is 19-21kV, the heating current is 0.9-1.6A, the target feed rate is 0.56-0.82mm / min, the part rotation rate is 8-16rpm, and the part preheating temperature is 850-950℃.
10. The method for preparing a self-repairing thermal barrier coating for a gas turbine blade according to claim 5, characterized in that: In S7, after the thermal barrier coating is prepared, the coating is subjected to diffusion heat treatment at a temperature of 1000-1060° C., a heating rate of 5-8° C. / min, and a holding time of 2-5 h; then, the coating is cooled to 70° C. by filling with argon gas and then taken out of the furnace.
Citation Information
Patent Citations
Multi-layer structure self-repairing thermal barrier coating layer and preparation method thereof
CN109778102A
Thermal barrier coating for turbine guide blade and compounding process of thermal barrier coating
CN117364010A
High temperature component, gas turbine high temperature component and manufacturing method thereof
US6398503B1
Cited By
Plating method for self-repairing anticorrosive coating on brass surface
CN120350340A